Leaf oils of the Australian species of Clausena and Micromelum (Rutaceae). Issue 5 (2nd September 2016) - Brophy, Joseph J.; Forster, Paul I.; Goldsack, Robert J.
Abstract: The leaf essential oils of Micromelum minutum, Clausena brevistyla and C. smyrelliana, all growing in Australia, have been investigated. M. minutum gave an oil in which the major components were the sesquiterpenes δ-elemene (3.3–18.6%), β-caryophyllene (4.8–30.3%), germacrene-D (2–15.8%) and germacrene-B (3.9–34.3%). C. brevistyla gave an oil rich in monoterpenes in two cases and sesquiterpenes in a third case. The principal components were myrcene (72.4%) or limonene (83.3%) for the monoterpene varieties and β-caryophyllene (19.4%), α-humulene (4.3%), bicyclogermacrene (9.5%), caryophyllene oxide (7.6%) and spathulenol (10.6%) for the sesquiterpene variety. C. smyrelliana gave an oil which was monoterpenic in nature with the principal component being α-pinene (73.3%), with β-caryophyllene (8.5%) as the next most abundant component.